Acerca de la recategorización interaccional de los marcadores discursivos - Baran, Marek (Neophilologica, 2012)
The subject of the article are discourse markers examined from the point of view that reaches beyond concentrating on text coherence and cohesion, or the information structure. It is postulated that discourse markers be analyzed as interactional markers whose communicative function may be defined through terms typical of linguistic politeness ( face-work; FTA vs FFA, positive politeness vs negative politeness), subjectivisation process, or interpretative tools of sociopragmatic conversational analysis.